The influence of learning environment and motivation on student achievement: a case study - Dyah Pikanthi Diwanti; Dwi Wahyu Pril Ranto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the impact of the learning environment and motivation on student achievement, with productivity as an intervening variable. Using PLS-SEM for data analysis, the study surveyed 159 active students from Universitas Muhammadiyah Yogyakarta (UMY) and STIB Kumala Nusa, employing convenience sampling. The findings indicate that the learning environment and motivation significantly influence learning productivity. However, while the learning environment directly affects student achievement, motivation does not. Additionally, learning productivity does not mediate the effects of either the learning environment or motivation on achievement. These findings show that a supportive learning environment helps improve both learning productivity and achievement. Meanwhile, motivation enhances productivity but does not contribute to learning achievement.